Performance of Turbo-Codes with Some Proposed Interleaver Schemes - Hadi, Ahmed S. (Al-Khwarizmi Engineering Journal, 2017)
This paper describes a number of new interleaving strategies based on the golden section. The new interleavers are called golden relative prime interleavers, golden interleavers, and dithered golden interleavers. The latter two approaches involve sorting a real-valued vector derived from the golden section. Random and so-called “spread” interleavers are also considered. Turbo-code performance results are presented and compared for the various interleaving strategies. Of the interleavers considered, the dithered golden interleaver typically provides the best performance, especially for low code rates and large block sizes. The golden relative prime interleaver is shown to work surprisingly well for high puncture rates. These interleavers have excellent spreading properties in general and are thus useful for many applications other than Turbo-codes.